Uji Aktivitas Sitotoksik dan Antioksidan Ekstrak Daun Keladi Tikus (T yphonium divaricatum (L) Decne) - YUNAHARA FARIDA; TITIEK MARTATI; AHMAD MUSIR; BERNARD EDWARD (JURNAL ILMU KEFARMASIAN INDONESIA, 2010)
Cytotoxic and antioxidant activities of Typhonium divaricatum (L) Decne leaves extract have been explored. Preliminary phytocheinical screening on the extract were carried out for the compound`s profile. Biological activity was measured by using Brine Shrimp Lethality Test (BSLT), while cytotoxic activity was conducted on breast cancer cell line T-47D using MTT method, Antioxidant activity was measured by using DPPH free radical scavenging method. The results of phytochemical screening showed that the methanol extract contained Havonoid, saponin and steroid/triterpenoid compounds, meanwhile thc n-hexane extract contained steroid/triterpenoid compounds only. The highest biological activity was found in methanol extract (IC50 = 32.9 ppm). The highest cytotoxic activity was shown by n-hexane extract (IC50 = 32.50 ppm). The highest antioxidant activity using vitamin C as positive control was found in methanol extract (IC50 = 56.63 ppm). The preliminary results indicated that Typhonium divaricatum (L) Decne lcavcs is potential for anticancer and free radical scavenger.